Assessment using photogrammetry technique - Ngai, Jia Le (2015)
Surface roughness of rock joint has always been the major consideration on the estimation of the shear strength of the rock mass which is one of the major research focuses in rock engineering. Digitalization of the rock surfaces to form 3-dimensional point cloud and extract directional roughness profiles is an alternative way to analyse the shear strength of the rock apart from conducting direct shear tests. The present process of rock surface digitalization was divided into two steps: 1) close range photogrammetry and 2) formation of digital rock surface profile. The accuracy that can be achieved by the close range photogrammetry was being assessed. Height of the objects, which is one of the factors affecting the accuracy, was investigated to identify the optimal height of the object that gave the most precise and accurate result. Four interpolation methods available in Matlab, which is the software that was used to analyse the point cloud were compared to determine the optimal method to reproduce the roughness surface of the rock. The Matlab programme was assessed to make sure the point cloud was adjusted correctly before the analysis of the surface roughness was carried out. Eight planes were created to assess the rotation of the point cloud following Euler’s theorem and the problems encountered were resolved. Estimation of Z2 values of two pairs of rock specimens obtained from the Brazilian tensile test failed in tension by using the assessed close range photogrammetry method and method of formation of digital rock surface profile.